Analisis Ejaan Dalam Karangan Narasi Fiksi Siswa Kelas IX MTs Al Islam Bunut Tahun Pelajaran 2024/2025 - Risti Komala (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
This research is motivated by the importance of proper spelling usage in writing fictional narratives at the junior high school level. The fundamental question examined is how spelling errors appear in the fictional narrative compositions of 9th-grade students at MTsS Al Islam Bunut and what types and frequencies of those errors occur. The researcher positions themselves as an observer and linguistic analyst focusing on orthographic aspects based on the General Guidelines for Indonesian Spelling (PUEBI). This study employs a descriptive qualitative approach with documentation techniques to collect data in the form of students’ fictional narrative essays. The data were analyzed through the stages of identifying, classifying, and interpreting spelling errors found. The results show that the most dominant spelling error is the misuse of capital letters, followed by incorrect use of prepositions and conjunctions, as well as incorrect compound word formations. From 30 student compositions analyzed, more than 150 spelling errors were found across various categories. These findings indicate the need for more focused and integrated spelling instruction in narrative writing lessons. Based on these results, it is expected that teachers can design more effective teaching strategies to improve students’ writing skills, particularly in the area of spelling.